Corporate venture capital no sistema regional de inovação: a percepção das grandes empresas tradicionais industriais da Região Metropolitana de Curitiba sobre o investimento em startups - Turetta, André Luiz (2019)
Large, traditional and industrial companies (LTIC) are important to Curitiba’s microregion. They create formal jobs and contribute with expressive taxes. Also, technology startups have a social impact, once they foster new knowledge-based business. This research aims to discover and understand what LTIC from Curitiba industrial district think about Corporate Venture Capital as a tool for funding new startup businesses in the region. It’s obvious the difficulty for Brazilian companies to get funds to invest in innovation. It's the case of the startups with a disruptive idea, when the risk is high and it turns impossible for them to access money with traditional banks. In the other hand, big companies like the industries from this study, has cultural and speed challenges to go through before innovating, mainly when the opportunity rely on a new matter, different of the core business. Situation essentially different from startup firms’ spirit. Through survey answered by 29 companies and a focal group applied to eight innovation managers, this work could gather quantitative and qualitative data to understand the pros and cons in CVC as a tool to connect startups and stablished business seeking innovation or competitive advantage. It was possible to find out that a minor part has an active CVC activity, and even though there are positive intentions on establishing CVC in the future, LTIC emphasize the risk and the cultural factors as important barriers to be overcome before assuming private equity. The research results indicate that a differentiated startup investment (or indirect) model, such as support or new business acceleration programs, in partnership with other RIS actors, would be more attractive than the traditional CVC. It could be happen initially excluding the private equity aspect and replacing it with other types of contribution, at least until LTIC build the cultural and functional maturity necessary to directly commit their financial resources.